Linguistic features of internet advertising in the english language - Cherniak, Oksana P. (My University, 2024)
In the modern world, advertising plays an extremely important role. At the current stage of technology development, Internet advertising is becoming increasingly popular, as it is Internet communication that allows combining the capabilities of all traditional printed and electronic media. Internet advertising is extremely diverse in terms of the advertising object, style, structure, and the use of speech means of influence. The purpose of the article is to analyze the linguistic factors that ensure the effectiveness of the Internet advertising discourse.
Keywords: Internet advertising; linguistic techniques; hyperbole; evaluative vocabulary; connotative adjectives; 001 (063)